Phytochemical composition and chemical profiling of extracts of Cordia grandicalyx Oberm - Mildred A. Chauke; Motetelo A. Mogale; Ladislaus K. Mdee; Leshweni J. Shai (Journal of Medicinal Plants for Economic Development, 2022)
Background: The search for bioactive organic products for the treatment of various diseases is a growing concern worldwide, because these bioactive natural products are associated with fewer side effects and are easily accessible.